Effect of alcoholic extract of the plant Nigella Sativa on viability of eggs and adults of the liver giant worm Fasciola gigantica In vitro. - Shlash, Shaimaa Abdul Hussein (University of Thi-Qar Journal of Science, 2014)
The study aimed to examine the effect of Nigella sativa extract on viability of eggs and adults of Fasciola gigantica In vitro. N.sativa brought from local markt of Al-Najaf city while eggs and adults worm of the parasite collected from cows and buffaloes infected and in the abattoir of Al-Najaf city.Result showed a significant effect for extract in reducing of the percentage of egg hatching and increasing of the mortality percentage of adult worms compar with control groups.